Search for the charged Higgs boson in the decays of top quark pairs in the eτ and μτ channels at √s=1.8 TeV - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amendolia, SR; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Asakawa, T; et al. (2000)
Top quark production offers the unique opportunity to search for a charged Higgs boson (H±), as the contribution from t→H+b→τ+νb can be large in extensions of the standard model. We use results from a search for top quark pair production by the Collider Detector at Fermilab (CDF) in the eτ+Slashed E signT+jets and μτ+Slashed E signT+jets signatures to set an upper limit on the branching ratio of ℬ(t→H+b) in 106 pb-1 of data. The upper limit is in the range 0.5 to 0.6 at 95% C.L. for H+ masses in the range 60 to 160 GeV, assuming the branching ratio for H+→τν is 100%. The τ lepton is detected through its 1-prong and 3-prong hadronic decays. ©2000 The American Physical Society.